TINJAUAN HUKUM TERHADAP KEBIJAKAN GUBERNUR DKI JAKARTA MENGENAI LOCKDOWN DALAM RANGKA PENANGANAN VIRUS COVID-19 - Dina Amelia, (2021)
The appearance of a new virus called Coronavirus that first appeared in Wuhan, China, became one of the problems in the world. In handling Covid-19, the government released several policies. One of them is by releasing the Governor's Regulation regarding the Implementation of Large- Scale Social Restrictions Concerning in Handling Covid-19 in the Province of DKI Jakarta. The regulation is guided by the Laws and Regulations above, which is the Ministry of Health's Regulations. This study uses an analysis-descriptive research method with a juridical-normative approach. The data are obtained from several Regulations such as Governments Regulations, some other regulations and policies, literature, and phenomenon in the field. The result of this research is the need for Governor policy in the form of a regulation and to tell the difference between the newest regulation with the previous regulation about lockdown in Jakarta. It also needed the higher laws and regulations, which is Regional Regulation, to strengthen the existing Governor Regulations.